Sinonasal outcome after endoscopic mononostril transsphenoidal surgery: A single center cohort study - Linsler, Stefan; Prokein, Benjamin; Hendrix, Philipp; Oertel, Joachim (Journal of Clinical Neuroscience, 2018)
Objective: The endoscopic endonasal approach has been well established for skull base surgery. However, there are only few studies pointing out nasal complaints after surgery. In this study, the authors evaluated postoperative nasal complaints and complications after mononostril endoscopic procedures. Methods: All patients operated on parasellar and sellar pathologies at our department via an endoscopic mononostril transnasal transsphenoidal approach from January 2011 to May 2015 were analyzed. To assess specific postoperative nasal pathological conditions and complaints, a questionnaire was established. Applicable data of 79 patients with additional ENT follow-up could be included. Endpoints were the quantitative evaluation of complications and correlation of these data. Results: There was no vascular injury or worsening of visual function. Two patients had persisting CSF fistula and one of them meningitis. There was a significant decrease of nasal complaints during follow up after 2 years (p < 0.001). Further surgical treatment by ENT physician was necessary in 11.4%. Resurgery significantly increased the risk of postsurgical complaints (p < 0.005). The use of a tamponade significantly reduced the risk of postsurgical reduced nasal airflow (p = 0.026) and sinusitis (p = 0.002). Conclusions: Endoscopic endonasal procedures to skull base lesions achieve high radicality with low complication rates. However, they induce temporary and permanent nasal complaints and complications. Thereby, resurgeries increase the risk of nasal complaints and the use of nasal tamponades might increase the sinonasal outcome. Further prospective studies are necessary to objectify the evaluation of postsurgical nasal complications.
CRIS-Team Scopus Importer:2023-12-20
Keywords: Endoscopic mononostril transsphenoidal approach; Nasal complaints; Sinonasal outcome; Skull base surgery